Object models : - Coad, Peter (Yourdon Press, 1997)
Connie's convenience store (A point-of-sale application); Wally's warehouse (a warehouse application); Ollie's order center (an order-entry application); Dani's diverters (a soft real - time conveyance application); All five application, at high speed; Strategies and patterns handbook.